O Programa Mais Educação na Diretoria de Ensino da região de Marília-SP - Mathias, Sônia de Lourdes Assuino [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study's goal is to discuss whether the Programa Mais Educação (PME), More Education Program in free translation, presented as a full-time school public politic, effectively constitutes an educational public politic, with the purpose of promoting the full-time education, as well as to present data demonstrating its evolution comparatively to the federal, São Paulo state and Regional Education Board of Marília city. The PME was created by the Brazilian Federal Government in the year of 2007 and implemented in the public basic education starting in 2008, promoting an increase in the studying hours by including socio-educative activities after class hours. Along this work, key differences between a full-time education and a full-time school are presented, from the conceptual basis offered by Classical thinkers who already discussed an individual's full-time education, through the Enlightenment, until contemporary New School intellectuals, who deal with the renovation of teaching and strongly influence the Brazilian educational thinking. Full-time school models idealized and implemented by Anísio Teixeira and Darcy Ribeiro are highlighted, as well as the full-time education concept by Paulo Freire. These three Brazilian intellectual's works and the role in the country's public life in the education area provided the foundations for the implementation of other full-time school models in Brazil, including the Programa Mais Educação. Discussion of all the foregoing leads to the understanding the PME's implementation was, in certain moments, done in disagreement to its own legislation. Its territorial distribution is presented with little transparency and its offer is restricted to portion of the students of each school, leading to the conclusion that, more than a state public education politic, the PME carries the name, shape and methods related and subordinated to whoever is, at the time, leading the country's educational...

Este estudo investigou se o Programa Mais Educação (PME), instituído como uma política pública de escola de tempo integral, constitui-se efetivamente numa política educacional com o propósito de estimular a educação integral. Buscou-se, também, apresentar dados que demonstram sua evolução de forma comparativa entre as esferas federal, estadual paulista e da Diretoria de Ensino da Região de Marília (SP). O PME foi criado pelo Governo Federal no ano de 2007, e implementado na rede pública de educação básica a partir de 2008, promovendo ampliação da jornada pela inclusão de atividades socioeducativas no contraturno escolar. São apresentados, ao longo do trabalho, aspectos essenciais que marcam a diferença entre educação integral e escola de tempo integral, desde a base conceitual oferecida pelos pensadores da Antiguidade Clássica, que já discutiam a educação integral do indivíduo, passando pelo Iluminismo, até chegar aos intelectuais contemporâneos do escolanovismo, que trataram da renovação do ensino e exerceram forte influência no pensamento educacional brasileiro. São destacados os modelos de escola de tempo integral idealizados e implementados por Anísio Teixeira e Darcy Ribeiro, e a concepção de educação integral de Paulo Freire. As obras e a participação na vida pública do país desses três intelectuais brasileiros, na área da educação, serviram de fundamentação para a implementação de outros modelos de escola de tempo integral no Brasil, inclusive o Programa Mais Educação. Os resultados da pesquisa sugerem que a implementação do PME foi, em determinados momentos, feita em desacordo com a própria legislação que o rege. Sua distribuição territorial apresenta-se de forma pouco transparente, e sua oferta é restrita a apenas uma parcela do alunado da mesma unidade escolar, permitindo concluir que, mais que uma política pública de Estado, o PME tem nome, desenho institucional e...
Keywords: Educação integral; Políticas públicas; Educação e Estado